Simultaneous Determination of Alogliptin and Pioglitazone in Human Plasma by a Novel LC-MS/MS Method - Praveen, Duddukuru Sri Sesha Sai; Asha, Syed; Pigili, Ravi K. (Current Pharmaceutical Analysis, 2020)
Background: A combination of alogliptin and pioglitazone is well tolerated. It does not increase the risk of hypoglycemia. In order to study the bioavailability of aloglipitn in the presence of pioglitazone, it is essential to have a method that can simultaneously detect both in human plasma. A protein precipitation-based method was used to determine alogliptin and pioglitazone simultaneously in human plasma. Protein precipitation causes ion suppression or enhancement in detection methods when compared to other methods. Objective: To simultaneously quantify alogliptin and pioglitazone in human plasma by LC-MS/MS based method. Methods: LC-MS/MS method for the simultaneous determination of pioglitazone and alogliptin in human plasma using stable isotope labelled compounds internal standards. The simple and one step solid phase extraction (SPE) was employed to extract the analytes from plasma. The extracted samples were separated on a C18 column by using a 25:75 (v/v) mixture of acetonitrile and 5 mM ammonium formate as the mobile phase at a flow rate of 0.5 mL/min. Results: The calibration curves obtained were linear (r2= 0.99) over the concentration range of 12.0- 2438.0 ng/mL for pioglitazone and 1.0-202.0 ng/mL for alogliptin. The results of the intra- and interday precision and accuracy studies were found to be within the acceptable limits. The analytes were stable under different stability conditions. All the validation results were found to be within the acceptable limits. The total analytical run time was 3.0 min. There was no interference from plasma matrices. Conclusion: The developed method is precise and adequately sensitive for detection and quantification of analytes. Thus, the method can be useful for bioavailability and bioequivalence (BA/BE) studies and routine therapeutic drug monitoring with the desired precision and accuracy.
Keywords: HPLC